Crustaceans as Key Prey: Insights Into the Dietary Partitioning of Four Carnivorous Fishes in the Nansha Islands, South China Sea - Chen Zhang; Simin Hu; Xianzhi Lin; Hui Huang; Sheng Liu (Ecology and Evolution, 2025)
ABSTRACT Small carnivorous fishes serve as important mesopredators in coral reef ecosystems. However, the habitat and prey availability degradation within these ecosystems has intensified the trend of body size miniaturization and interspecific competition among these species. To better understand the food selection and resource partitioning strategies of mesopredators, we conducted a comprehensive study on the feeding habits of four small carnivorous fish species collected from the coral reefs of the Nansha Islands. This study employed a combination of morphological analysis and molecular identification of gut contents, along with stable isotope analysis. Similar food items, mostly semi‐digested/undigested body remains/fragments from crustaceans, fish, and mollusk were detected in the guts of the analyzed fishes. High‐throughput sequencing based on DNA barcoding identified approximately 24 taxa belonging to Arthropoda, Chordata, and Mollusca, with Arthropoda being the most abundant prey group, accounting for 82.2%–92% of the total sequences across the four fish species. Stable isotope analysis further revealed that the trophic levels of the four species ranged from 3.4 to 3.6. The results of food overlap analysis based on stable isotopes contrasted with those obtained from high‐throughput sequencing, highlighting the distinct characteristics and complementary strengths of these methods. This study broadens the current understanding of the feeding ecology of four carnivorous fish species. The findings reveal that crustaceans are the primary food source for carnivorous fishes in the Nansha Islands, differing from previous assumptions that their diets were predominantly fish‐based. Additionally, the differentiated utilization of crustacean resources among these species suggests that marine benthic invertebrates may play a crucial role in supporting mesopredators within degraded coral reef ecosystems, potentially helping to mitigate the environmental stress they face.